Pre-treatment of oil palm frond biomass via extensive high temperature drying for gasification process - Mat Razali Nur Hazwani; Sulaiman Shaharin Anwar; Zaidi Moni Mohamad Nazmi; Basrawi Mohamad Firdaus (MATEC Web of Conferences, 2017)
Oil palm frond has been utilized as a solid biomass fuel for gasification to produce synthesis gas or syngas to be used for heat and power generation. A fuel pre-treatment method by means of extensively-drying OPF blocks at 150°C and 200°C for 4 hours was implemented to investigate the effects of the fuel in terms of drying efficiency and gasification performances. Tar, pyrolysis oil and condensates were found to be squeezed out by heat during drying, signifying volatilization of fuel at temperatures between water boiling point at 100°C and fuel pyrolysis point at 280°C. Syngas produced from the updraft gasification of extensively-dried OPF blocks was analyzed and tested for sustainable gas flares. The syngas was found to be composed of 16.5% CO, 10% CO2, 4% H2 and 0.9% CH4 and was produced at gasification temperatures lower than that exhibited by normal OPF blocks.